Critical digital humanities : the search for a methodology - Dobson, James E. (Topics in the digital humanities., 2019)
"Can established humanities methods coexist with computational thinking? It is one of the major questions in humanities research today, as scholars increasingly adopt sophisticated data science for their work. James E. Dobson explores the opportunities and complications faced by humanists in this new era. Though the study and interpretation of texts alongside sophisticated computational tools can serve scholarship, these methods cannot replace existing frameworks. As Dobson shows, ideas of scientific validity cannot easily nor should be adapted for humanities research because digital humanities, unlike science, lack a leading-edge horizon charting the frontiers of inquiry. Instead, the methods of digital humanities require a constant rereading. At the same time, suspicious and critical readings of digital methodologies make it unwise for scholars to defer to computational methods. Humanists must examine the tools--including the assumptions that went into the codes and algorithms--and questions surrounding their own use of digital technology in research. Insightful and forward thinking, this book lays out a new path of humanistic inquiry that merges critical theory and computational science"--